Managerial decision cases - Finnegan, Thomas. (South-Western College ; Thomson Learning, 2001)
Introduction. Basic concepts. Activity cost behavior. Activity-based costing (ABC). ABC and ABM. Job order costing. Process costing. Cost allocation. Budgeting. Variance analysis...